The Effect of Pharmacist Counseling on Knowledge of Hypertension Treatment: A Narrative Review - Amandha Baruni; Andika Nicholas Iqbal Ardiansyah; Anisa Rahayu; Nuning Nuning; Vallina Laurensia Indika Ningrum; Akhmad Azmiardi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Hypertension is a chronic condition that requires long-term medication adherence to prevent serious cardiovascular complications. Adequate knowledge about treatment is an important prerequisite for patients to achieve optimal adherence. Pharmacists play a crucial role in providing education and advice through medication counseling. Objective : This review aims to synthesize evidence narratively regarding the effect of counseling interventions conducted by pharmacists on improving patients' knowledge about hypertension treatment Research Methods/ Implementation Methods : This narrative review was conducted by tracing various relevant research articles. Article searches were carried out on the PubMed, Google Scholar, and ResearchGate databases, with publications from 2011 to 2022. The main keywords used included "pharmacist counseling," "medication knowledge," and "hypertension." Article criteria included medication counseling provided by pharmacists to patients. Inclusion criteria for articles were knowledge level as an outcome, articles written in Indonesian or English, and being full-text articles. After screening based on the criteria, 15 research articles were selected for narrative analysis. Results : The results of the literature review from 15 analyzed articles consistently show that counseling provided by pharmacists has a positive and significant impact on improving patients' knowledge about hypertension treatment. The majority of studies reported measurable increases in patients' understanding of dosage regimens, drug-food interactions, side effect management, and the importance of blood pressure monitoring. Effective counseling helps address knowledge gaps that often act as barriers to good medication adherence. This increase in knowledge is often an important initial step before achieving improved adherence and better blood pressure control Conclusion/Lesson Learned : Pharmacist counseling is an effective intervention in enhancing the knowledge of hypertensive patients about their medications. These findings recommend that the healthcare system optimize the role of pharmacists in patient education to achieve better treatment outcomes.